Integrating Local Culture and Digital Tools in Culturally Responsive English Teaching - Nurteteng Nurteteng; Nursalim Nursalim; Melanie Bobert (JOLLT Journal of Languages and Language Teaching, 2026)
This study explores the integration of local cultural content and digital tools in culturally responsive English teaching at UNIMUDA Sorong, West Papua.The study emerged from the challenges of teaching English in multicultural and resource-diverse classrooms where students come from different linguistic, cultural, and technological backgrounds. In this context, English is often learned as a third or fourth language, while unequal access to digital resources continues to shape classroom participation. This study aimed to investigate how lecturers integrate local culture and digital tools in English learning and how students respond to these practices. This study employed a descriptive qualitative design involving 30 second-semester students and five English lecturers in the General English course at UNIMUDA Sorong. Data were collected through questionnaires, semi-structured interviews, and classroom observations and analyzed using data condensation, data display, and conclusion drawing or verification. The findings revealed four major themes. First, the integration of Papuan cultural content increased students’ motivation and confidence across speaking, reading, listening, and writing activities. Second, digital platforms such as YouTube, Instagram, and TikTok supported student engagement and encouraged more interactive English learning experiences. Third, unequal internet access and differences in digital literacy limited some students’ participation in technology-based activities. Finally, lecturers played an important role as mediators who connected local culture with digital learning practices in multicultural classrooms. The study suggests that integrating local culture and digital tools can support more inclusive and meaningful English learning in culturally diverse contexts. However, institutional support and equitable digital access remain essential for the sustainable implementation of culturally responsive and technology-enhanced pedagogy in Eastern Indonesia.